CDX-2, MUC-2 and B-catenin as intestinal markers in pure mucinous carcinoma of the breast - García Labastida, Laura Elvira; Garza Guajardo, Raquel; Barboza Quintana, Oralia; Rodríguez Sánchez, Irám Pablo; Ancer Rodríguez, Jesús; Flores Gutiérrez, Juan Pablo; Gómez Macías, Gabriela Sofía (2014)
Background: Pure mucinous adenocarcinoma of the breast is a rare entity characterized by the production of variable amounts of mucin comprising 1% to 6% of breast carcinomas. Some mucinous adenocarcinomas have shown expression of intestinal differentiation markers such as MUC-2. This study examines the expression of intestinal differentiation markers in this type of breast carcinoma. Results: Twenty-two cases of pure mucinous adenocarcinoma of the breast were assessed. Immunochemistry was performed for beta-catenin, CDX-2 and MUC-2. All cases were positive for B-catenin. MUC-2 positivity was observed in all cases; 63. 6% were 3 plus positive. All cases were negative for CDX-2. Conclusions: These results suggest that mucinous breast carcinomas express some markers of intestinal differentiation, such as MUC-2 and beta-catenin; however, future studies with a larger series of cases and using molecular techniques that help affirm these results are needed.